Local gauge symmetries applied to Physics - Huamani Chaviguri, Richard (2011)
In this paper we give a simple description about the local gauge symmetries both abelian and non abelian and subsequent fundamental physics applications emerging for each particular gauge transformation such as Quantum Electro Dynamics, QED, Quantum Cromo Dynamics, QCD and lepton field.